Sustainability Aspects of Precision Agriculture for Row Crops in Florida and the Southeast U.S. - David L. Wright; James J. Marois; Jimmy R. Rich (EDIS)
This document is SS-AGR-184, one of a series of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published October 2002.